PENGARUH BRAND AMBASSADOR, CUSTOMER REVIEW DAN LAYANAN CSH ON DELIVERY TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI APLIKASI SOCIAL COMMERCE. - Sihaloho, Wilda Thoma; Patrikha, Finisica Dwijayati (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
The purpose of this study was to determine the effect of Brand Ambassador (X1), customer reviews (X2) and cash on delivery services (X3) on consumer purchasing decisions (Y) in social commerce applications. the type of research used is quantitative. The population used is consumers of social commerce applications who have purchased fashion products with a total of 136 samples used. Sampling is sought using the lemeshow formula because the population is an infinite population where the exact number of populations is not known, and uses a purposive sampling method. For data collection techniques, researchers use questionnaires with dissemination via googleforms and to carry out data processing using PLS (Partial Least Square) data analysis techniques with SEM analysis methods using SmartPLS 3 with tests namely (1) measurement of external models/models, (2) structural models / model in and (3) hypothesis test. Based on the results of data processing, it was obtained (1) The test results showed that the original sample X1 value for Y 0.278, the t-statistic value 2.367 and the p-value 0.018 and the t-statistic greater than 1.96 and the p-value smaller than 0.05 and has a (+) relationship because the original sample is close to +1. So that Brand Ambassadors influence consumer decisions to buy in social commerce applications. (2) The test results show that the original sample X2 to Y is 0.737, the t-statistic is 7.576, and the p-value is 0.000 and the t-statistic is greater than 1.96, and the p-value is less than 0.005 and The relationship has a positive because the original sample is close to +1 so that customer reviews have a (+) influence on consumer purchasing decisions in social commerce applications. (3) The test results show that the original value of sample X3 to Y is -0.188, the t-statistic value is 1.906, and the p-value is 0.057 and the t-statistic is greater than 1.96, and the p-value is less than 0.005 and the relationship has a (-) because the original sample is close to -1 so that the cash on delivery service has no effect on consumer purchasing decisions in social commerce applications.